HEAVY METALS IN URBAN ROAD SEDIMENTS OF THE CITY OF MEXICALI, MEXICO - Lourdes Monserrat MEZA TREJO (Revista Internacional de Contaminación Ambiental, 2014)
A chemical sediment characterization of urban streets in the city of Mexicali at Baja California, Mexico, was conducted to estimate the most important heavy metals along with PM 10 and PM 2.5 emission factors (EF) to evaluate the amount of particulate matter. Sampling was conducted from february to may 2008, following a random statistical design, in 60 sampling sites on a georeferenced map at UTM 11 North. Samples were identified and treated in the laboratory, after undergoing cracking, drying, sieving, and weighing to get less than 75 microns of sediment by using a dry method. Twelve representative samples were selected for chemical characterization using energy dis - persive X-rays (EDX) and inductively coupled plasma (ICP). The most significant elements found were zinc (Zn) and lead (Pb) with concentrations ranging from 1 to 15 mg/kg and 11 to 25 mg/kg, respectively, corresponding to the third classification from a reference set of a study by US EPA in 1981-1997. The clay type known as illite was identified in four specific samples